Imagination of the North in Context of Development of Natural Environment: Mammoth in Mythological Representations of Yakuts - O. V. Vasilyeva; A. A. Kuzmina; A. R. Fedorova (Научный диалог)
A number of negative characters in Yakut mythology, as well as individual images of folklore, are considered. The point of view, according to which the basis for the emergence of certain mythological ideas among the Yakuts was the real world, the features of the landscape and climate, to the extent that they influenced a person, is proved. It is noted that the culture of the Sakha people is based on rich mythological concepts that have developed during the development of the vast expanses of the Arctic space. The authors analyze ethnographic notes of the XIX—XX centuries and modern scientific publications, which examine the mythology and folklore of the Sakha people (Yakuts). An attempt has been made to clarify the question of the influence of knowledge about the fossil remains of the mammoth fauna on the formation of mythological ideas related to the peculiarities of the climate of the region being developed. The image of a mammoth is analyzed in the broad context of the mythological views of the Yakuts. It is concluded that secondary esoteric ideas about mammoths, caused by the discovery of their remains, could form the basis of a prototypical image for a number of characters in Yakut mythology, for example, a water bull and a cold bull. It is proved that the idea of mammoths could be reflected in the external appearance of the abaasy heroes in the epic folklore of the Sakha.